WASHING LIQUID FOR PERVINNOGO OPENING OF PRODUCTIVE LAYERS ON DEPOSITS LOCATED IN RECREATSIYNIH AREAS - Коцкулич, Ярослав Степанович; Тершак, Богдан Андрійович; Коцкулич, Євген Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It has been developed a component composition of the drilling fluid containing castor oil as a hydrocarbon phase instead of oil. The results of researches of drilling fluid’s technological features using developed ecological friendly chemical reagents of organic colloid “Premix O” and antifoam agent “Premix D” were listed.